Finite element simulation and integration of CEM43 °C and Arrhenius Models for ultrasonic-assisted skull bone grinding: A thermal dose model. (April 2021) - Babbar, Atul; Jain, Vivek; Gupta, Dheeraj; Agrawal, Deepak
Highlights: Use of a novel ultrasonic-assisted in-house developed setup for skull bone grinding. Determination of the effect of varying process parameters on temperature rise during grinding. Development of a hybrid model for predicting tissue damage during bone grinding. Finite element simulation to measure the thermogenesis and osteonecrosis depth. Abstract: The aim of the study was to develop a novel automated setup for bone grinding to limit the temperature to below 43 °C. The feasibility of using ultrasonic actuation during bone osteotomy was explored with different machining variables, such as rotational speed, feed rate and ultrasonic frequency, in terms of the criterion variable (i.e., temperature). A thermal dose model based on the CEM43 °C and the Arrhenius model was developed for the prediction of tissue damage during bone grinding. CEM43 °C is a normalizing method to convert the time-temperature relationship into an equivalent number of minutes at 43 °C. For every degree rise in temperature above 43 °C, the cell viability significantly increased. The temperature generated during bone grinding was measured with an infrared thermography technique. The increase in temperature above threshold levels of 43 °C and 47 °C may harm the bone tissues and cause thermogenesis and osteonecrosis, respectively. A finite-element simulation was conducted to visualise the spatial and temporal distribution of temperature on the bone surface after bone grinding. Furthermore, simulation results were used to measure the depth of thermogenesis and osteonecrosis at the grinding site. Evaluation of the optimised set of bone grinding process parameters was supported with analysis of variance at the 95% confidence level.